2013
DOI: 10.1186/1471-2334-13-39
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the incidence and prevalence of genital warts

Abstract: BackgroundAnogenital warts (AGWs) are a common, highly infectious disease caused by the human papillomavirus (HPV), whose high recurrence rates contribute to direct medical costs, productivity loss and increased psychosocial impact. Because of the lack of a systematic review of the epidemiology of AGWs in the literature, this study reviewed the published medical literature on the incidence and prevalence of AGWs.MethodsA comprehensive literature search was performed on the worldwide incidence and prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
268
4
44

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(331 citation statements)
references
References 57 publications
(190 reference statements)
15
268
4
44
Order By: Relevance
“…The current prevalence of CA in pregnant women, with even higher rates among teenagers, is comparable to some previous observations in a range of sexually transmitted infections (8)(9)(10)(11)(12)(13). In previous studies that reported age-based estimates, younger participants showed higher prevalence of HPV or CA than older participants.…”
supporting
confidence: 66%
“…The current prevalence of CA in pregnant women, with even higher rates among teenagers, is comparable to some previous observations in a range of sexually transmitted infections (8)(9)(10)(11)(12)(13). In previous studies that reported age-based estimates, younger participants showed higher prevalence of HPV or CA than older participants.…”
supporting
confidence: 66%
“…The overall (females and males combined) reported annual incidence of anogenital warts (including both new and recurrent) ranged from 160 to 289 per 100,000. Incidence peaked before 24 years of age among females and between 25 and 29 years of age in males (Patel et al, 2013). …”
Section: Global Distributionmentioning
confidence: 99%
“…However, when HPV is transmitted from one person to another, the virus infects the top layers of the skin and can remain inactive or latent for months or possibly years before warts or other signs of HPV infection appear. Prospective studies reported that the median time between infection with HPV types 6 or 11 and the development of anogenital warts was 11 to 12 months among males, and 5 to 6 months among young females (Patel et al, 2013). …”
Section: Incubation Periodmentioning
confidence: 99%
“…The annual incidence of AGWs is 160-289 per 100,000 and the overall prevalence ranges from 0.13-0.56% (Patel et al, 2013). Human papillomavirus (HPV) infection type 6 and 11, which are non-oncogenic types, account for more than 90% of the clinical manifestations as being confirmed by a deoxyribonucleic acid (DNA) analysis of wart specimens (Ball et al, 2011).…”
Section: Introductionmentioning
confidence: 99%